Assessing key ecosystem functions through soundscapes: A new perspective from coral reefs. (December 2019) - Elise, Simon; Urbina-Barreto, Isabel; Pinel, Romain; Mahamadaly, Vincent; Bureau, Sophie; Penin, Lucie; Adjeroud, Mehdi; Kulbicki, Michel; Bruggemann, J. Henrich
Abstract: The functioning of tropical coral reefs is imperilled by climate change, overfishing, and decreasing water quality. Maintaining their capacity to provide goods and services will critically depend on our ability to monitor their functioning at appropriate spatial and temporal scales. Given the constraints of traditional methods to respond to those needs, the potential of complementary tools such as Passive Acoustic Monitoring (PAM) is emerging. Coral reef soundscapes (i.e. ambient sound) encompass sounds produced by numerous organisms. Soundscape characteristics quantified by ecoacoustic indices have been found to reflect general ecosystem properties, such as diversity and abundance of fishes, and coral cover. The present study tested, on the virtually pristine coral reefs around Europa Island, South-West Indian Ocean, the capacity of acoustic indices to assess key ecosystem functions. Soundscapes were recorded during 2 h, and ecosystem functions were evaluated using video footage of the fish assemblages and underwater photogrammetry of the benthic landscapes. We found significant and strong correlations between six ecoacoustic indices and six key ecosystem functions, including habitat features and fish assemblage characteristics. The six ecoacoustic indices were representative of several combinations of frequency, amplitude and time analysis domains, highlighting the diversity of the functional information conveyed by soundscapes. Our findings reveal that a 2 h daytime recording on a coral reef could provide sufficient acoustic information to characterise major ecosystem functions of a site. This should facilitate the detection of functional disturbances at temporal and spatial scales adapted to the rapidity of upcoming climate changes. Our results also highlight the potential of ecoacoustics to bring novel and relevant insights in the functioning of ecosystems.